Հայկական լեռնաշխարհի տեղանուններն ըստ Ն. Ադոնցի «Հայոց պատմություն» աշխատության - Գրիգորյան, Սոնա («Զանգակ - 97»)
In the second half of the 19th centuary the Armenian nation gave birth to several great personalities, who raised the Armenian studies to higher level. Among those great researchers N. Adontz must be mentioned. In the last period of his life he occupied himself with the research of the history of Biajnili-Urartu. The results of his research were posthumously published in 1946 in a voluminous work under the heading "History of Armenia".
Keywords: Հայկական լեռնաշխարհ; Հայոց պատմություն